UNIVERSAL DESIGN AND PEDESTRIAN BRIDGE ACCESSIBILITY IN THE VARDAR RIVER CORRIDOR, GOSTIVAR (NORTH MACEDONIA) - Menga, Levent (International Scientific Journal Vision, 2025)
Urban river corridors represent vital linear public realms that structure mobility, leisure, and ecological continuity within cities. Yet small discontinuities particularly at pedestrian crossings can produce disproportionately large accessibility losses, effectively marginalizing groups such as persons with disabilities, the elderly, and cyclists. This study investigates accessibility along the Vardar River corridor in central Gostivar, North Macedonia, with a specific focus on the most intensively used pedestrian bridge and its integration into the wider riverside path network. Employing a mixed-methods approach, field observations were combined with a trilingual survey of 100 residents aged 14–73. The analysis compared user experiences across age, mobility status, and bicycle use. Findings reveal pervasive barriers: 90% of respondents judged the bridge inaccessible overall; 100% considered it unsuitable for persons with disabilities; 76% reported inadequacy for cyclists (24% undecided, 0% “suitable”); and 73% found it problematic for elderly or pregnant users. Moreover, 88% of participants expressed a preference for ramped access over stairs, while 53% supported the construction of a new, universally accessible bridge. The study concludes that deficiencies in the bridge network, rather than shortcomings in park amenities, constitute the primary barrier to equitable use of the riverfront. A context-specific design proposal is advanced ~30 m span, 2.5 m width, ≤8% ramp slopes with rest landings, tactile surfaces, and continuous handrails explicitly grounded in the Seven Principles of Universal Design and aligned with the European Accessibility Act (2019) and EN 17210 standards. Accessibility here is framed not as a supplementary feature but as a fundamental principle of contemporary urban public space.